EXTRACTION OF BIOACTIVE COMPONENTS OF KETEPENG CINA (Senna alata L.) LEAFS USING ULTRASONIC AND MACERATION METHODS ON VARIOUS SOLUTION CONCENTRATIONS - Avif, Adnan Nur; Yaqhsa, Ardhi Billih (Jurnal Penelitian Pascapanen Pertanian, 2021)
Ketepeng cina Senna alata L. is one of the plant species growing in the tropical climate whose leaves have various bioactive components. It has been used as a traditional medicine to treat skin diseases. Ketepeng cina has been cultivated in several regions in Indonesia and the results are exported abroad to be used as medicinal raw materials. So far, the plant extraction process is still using the maceration method. This method is simple but has weaknesses in time consumption making it less efficient. The extraction method by ultrasonic waves promises more efficient extraction process than the maceration method. The purpose of this study was to determine the differences in extraction techniques and solvent concentration on the concentration of phytochemical constituents in ketepang cina leaves. The research design used a completely randomized design with two factorial patterns. The first factor was the technique of extracting Ketepeng cina leaves (maceration, ultrasonication), and the second factor was the concentration of solvent/ethanol (40%, 70%, 96%) The observation parameters included analysis of the content of total phenolic compounds, flavonoids, and tannins. The results showed that the use of the ultrasonication technique provided efficiency in extraction time compared to the maceration technique. The use of 70% ethanol resulted in higher concentrations of total phenolic and flavonoid compounds (28,17 mgGA/g) and (17,61 mgQE/g), but the highest concentration of tannins produced by 96% ethanol solvent was 6,78 mgAT/g.